A Review on Biological Aspects and Applications of Proteases - Iqbal, Iqra; Ashraf, Asfa (International Journal of Molecular Microbiology, 2020)
Proteases (also termed proteolytic enzymes or proteinases) are specific types of enzymes that play important roles in protein digestion, immune function, and other vital processes. Proteases are an integral component of existing life on earth, such as animals, plants, and microbes. Proteases are successfully considered as an alternative to chemicals and an eco-friendly indicator for nature or the surroundings. Proteolytic enzymes may aid the digestions of protein, reduce symptoms of irritable bowel syndrome, decrease inflammation, ease muscle soreness, and speed recovery after surgery. The creation and introduction of innovative technologies has greatly expanded the scope of application of enzyme preparations. This review presents the latest discoveries on the biological aspects of proteases, and their diverse field applications including food science and technology, pharmaceutical industries, detergent manufacturing, and biotechnology. Thus, proteases should be expected to maintain their prominent position in enzyme utilization and may have a future full of successful new applications.